2010
DOI: 10.1007/s11273-010-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring coastal wetland communities in north-eastern NSW using ASTER and Landsat satellite data

Abstract: The coastal wetland communities of north-eastern New South Wales (NSW) Australia exist in a subtropical climate with high biodiversity and are affected by anthropogenic and natural stressors such as urbanization and climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…This study has illustrated how careful analysis of remote sensing data using a GIS platform can lead to a detailed understanding of the growth and evolution of deltaic and estuarine systems and is similar to the results presented for other Australian coastal systems [3,4,19,[41][42][43]. This implies that the methodology can be broadly applied to study morphological changes over relatively short timeframes in other coastal lagoon systems both in eastern Australia and more generally to any similar systems around the world.…”
Section: Morphological Evolution Of the Wandandian Deltasupporting
confidence: 72%
See 1 more Smart Citation
“…This study has illustrated how careful analysis of remote sensing data using a GIS platform can lead to a detailed understanding of the growth and evolution of deltaic and estuarine systems and is similar to the results presented for other Australian coastal systems [3,4,19,[41][42][43]. This implies that the methodology can be broadly applied to study morphological changes over relatively short timeframes in other coastal lagoon systems both in eastern Australia and more generally to any similar systems around the world.…”
Section: Morphological Evolution Of the Wandandian Deltasupporting
confidence: 72%
“…Many coastal ecosystem management strategies have become more focused on the conservation and sustainability of coastal wetlands [1,2] locally [3], regionally [4] and globally [5] according to their unique ecosystem function roles [6]. However, they are located in sensitive zones where anthropogenic and climate change stressors are concentrated, such as estuaries and deltaic platforms [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The approach suggested here goes beyond the physiognomy-based approach to vegetation conducted on Landsat images by Baker et al, 2006;MacAlister and Mahaxay, 2009;Ottinger et al, 2013;Akumu et al, 2010;Cardoso et al, 2013;SanchezHernandez et al, 2007, as it provided information regarding the probable plant communities and thereafter probable species composition. It also proved successful to detect a wide range of habitat types, even when combined in a fine-grained landscape, and including both inland and tidal marshes.…”
Section: Discussion Vegetation Classifications In Coastal Marshes Usimentioning
confidence: 99%
“…The procedure that we tested in this work consisted in aggregating fine-grained vegetation units that constitute repetitive combinations at a higher hierarchical level. In most Landsat-based studies, the vegetation is aggregated according to physiognomy: Baker et al (2006) mapped woods, herbaceous and crops; Ottinger et al (2013) discriminated saline meadows from shrubs and broadleaved trees; Cardoso et al(2013) classified mangroves, marshes and dunes; Akumu et al(2010) characterized dunal wetlands, forested wetlands and coastal swamp; Sanchez-Hernandez et al(2007) identified satlmarshes and fens. Aggregation criteria may also be based on structural types, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2) involved the use of Landsat TM data acquired in February 2009, Digital Elevation Model, and a site specific information file in order to predict the potential impacts of sea level rise on the coastal wetlands. Preprocessing (geometric and radiometric corrections) and supervised classification of Landsat TM satellite data were carried out (Akumu et al 2010) in order to generate the wetland categories found in the north-eastern region of NSW using ER Mapper Version 7.1. The wetland categories classified were: Mangroves and saltmarshes, dunal wetlands, coastal swamps, coastal upland water bodies, estuarine water bodies and forested wetlands.…”
Section: Sea Level Rise Projectionmentioning
confidence: 99%